2022
DOI: 10.7759/cureus.24261
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Perioperative Atelectasis With Duration of Anesthesia, Pneumoperitoneum, and Length of Surgery in Patients Undergoing Laparoscopic Cholecystectomy

Abstract: Background During anesthesia, atelectasis is frequent, and it is also seen in critically ill individuals with a variety of underlying causes and pathologies. Objective The present study was conducted to assess whether there is a correlation between perioperative atelectasis and duration of anesthesia, pneumoperitoneum, and length of surgery in patients undergoing laparoscopic cholecystectomy. Material and methods Seventy-two American Society of Anesthesiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…General anesthesia can lead to the collapse of 10-15% of lung tissue [30]. The notable difference between this study and the one by Cinella et al [8] is the time point of the surgery where the RM was performed.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…General anesthesia can lead to the collapse of 10-15% of lung tissue [30]. The notable difference between this study and the one by Cinella et al [8] is the time point of the surgery where the RM was performed.…”
Section: Discussionmentioning
confidence: 65%
“…The PaO 2 /FiO 2 ratio demonstrated an increase of 63.8% before and after the RM. Patel et al [30] reported that even in short-term pneumoperitoneum (15-80 min), atelectases were found in the dependent part of the lung, as depicted on lung ultrasound intraoperatively. In a study by Monastesse et al [31], prolonged pneumoperitoneum was associated with an increased loss of aerated alveoli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies employ an ultrasonographic method of scoring lung pathology, namely the lung ultrasound score (LUS) (Table 1). A lung ultrasound score assessment is performed for multiple reasons, such as: perioperative oxygenation (31), predicting disease severity and mortality in ARDS (32), monitoring of lung aeration changes (after proning in ARDS, antimicrobial therapy in ventilator-associated pneumonia, selecting the ideal positive end-expiratory pressure, etc.) (33)(34)(35), weaning from mechanical ventilation (36), and as a prognosticator for respiratory failure (15, 18-20, 22, 28).…”
Section: Lung Ultrasound Scorementioning
confidence: 99%
“…However, CO 2 in ation causes surgical stress, changes in blood circulation, and pulmonary compliance, and it may even increase intracranial pressures [2][3][4]. Approximately 21.5%, 21.2%, and 30.3% of patients may have decreased forced vital capacity (FVC), forced expiratory volume in one second, and forced expiratory ow at 25-75% of FVC, respectively [5][6][7].…”
mentioning
confidence: 99%